2011
DOI: 10.1107/s0108270111013618
|View full text |Cite
|
Sign up to set email alerts
|

1,3,5-Tris(bromomethyl)benzene

Abstract: The asymmetric unit of the title compound, C(9)H(9)Br(3), is composed of a single molecule. Two bromo substituents are located on one side of the plane of the aromatic ring and the third is on the opposite side, with the molecular unit exhibiting an approximate noncrystallographic C(s) point group. The crystal structure is rich in Br...Br, CH(2)···Br and CH···π weak intermolecular contacts which mediate the crystal packing of individual molecules. These interactions promote a red-shift of a handful of vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Preparation of (benzene-1,3,5-triyltris(methylene)) triphosphonic acid (Benzene-1,3,5-triyltris(methylene))triphosphonic acid (H 6 bmt) was prepared by a two-step reaction according to published procedures with small modifications (Scheme 2). 20 Synthesis of H 6 bmt started with a Michaelis-Arbusov reaction of 1,3,5tris(bromomethyl)benzene 21 with triethyl phosphite at 120 C. Upon completion of the reaction the excess of triethyl phosphite was removed by distillation under reduced pressure. The intermediate compound L' [hexaethyl(benzene-1,3,5-triyltris-(methylene))tris(phosphonate)] was purified by flash column chromatography and isolated as a colorless oil in excellent yield (88%).…”
Section: Ligand Design Strategymentioning
confidence: 99%
“…Preparation of (benzene-1,3,5-triyltris(methylene)) triphosphonic acid (Benzene-1,3,5-triyltris(methylene))triphosphonic acid (H 6 bmt) was prepared by a two-step reaction according to published procedures with small modifications (Scheme 2). 20 Synthesis of H 6 bmt started with a Michaelis-Arbusov reaction of 1,3,5tris(bromomethyl)benzene 21 with triethyl phosphite at 120 C. Upon completion of the reaction the excess of triethyl phosphite was removed by distillation under reduced pressure. The intermediate compound L' [hexaethyl(benzene-1,3,5-triyltris-(methylene))tris(phosphonate)] was purified by flash column chromatography and isolated as a colorless oil in excellent yield (88%).…”
Section: Ligand Design Strategymentioning
confidence: 99%
“…Other papers have discussed the structures of all di(bromomethyl)naphthalene isomers [2], 1,6,7-tris(bromomethyl)naphthalene [3], 1,5-dibromo-2,6-dimethylnaphthalene [4], 2,5-bis(bromomethyl)-biphenyl [5], 2,2 -bis(bromomethyl)-p-terphenyl [6], mesitylene and dimesitylene compounds bearing bromomethyl units [7], a new polymorph of 1,4-dibromo-2,5-dimethylbenzene [8] and two polymorphs of 1,4-bis(tribromomethyl)benzene [9]. Other authors have reported the structure of 1,3,5-tris(bromomethyl)-benzene [10].…”
Section: Introductionmentioning
confidence: 99%